Expression of Receptor Activator of Nuclear – Kappa β Ligand in Patients with Metastatic Bone Disease - Magetsari, Rahadyan; Dwianingsih, Ery Kus; Budhiparama, Nicolaas Cyrillus; Araneta, Irene; Sakti, Yudha M. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Bone metastasis is a complication that often occurs due to cancer in solid organs, and more often compared to primary bone tumors. Bone metastasis is associated with excessive osteolytic processes. AIM: This study was conducted to reveal the correlation between Receptor Activator of Nuclear factor kβ Ligand (RANKL) expression, lactate dehydrogenase (LDH), and neutrophil-lymphocyte ratio (NLR) level in patients with bone metastatic lesions. METHODS: This cross-sectional study was conducted in 15 subjects with bone metastatic lesions. The specimens were fresh bone tissues obtained by open biopsy. Expression of RANKL in mRNA level was detected quantitatively using reverse transcription-polymerase chain reaction. LDH and NLR were analyzed from the peripheral blood analysis. The correlation of RANKL expression with LDH and NLR was statistically analyzed. RESULTS: This study enrolled 15 subjects with bone metastasis disease based on the clinical, radiological, and histopathological results. The means of LDH, NLR, and RANKL expression were not significantly different. There was no significant association between the characteristics of metastatic lesion and RANKL expression. The correlation between LDH levels with RANKL expression was positive (p < 0.05), while the correlation between NLR and RANKL expression was negative (p < 0.05). CONCLUSION: RANKL expression was positively correlated with LDH and negatively correlated with the NLR. Both LDH and NLR can be used as predictive factors of RANKL expression in bone metastasis.